The introduction of a secondary reinforcer during therapy based on the ABA model for children with autisme - Ban, Weng Lun; Susheel Kaur Dhillon Joginder Singh,; Kartini Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Applied Behavior Analysis (ABA) is a technique used to teach children with autisme a variety of skills. In ABA, children with autisme often do not receive reinforcers because they have difficulty performing their targeted behaviors, which consequently leads to challenging behaviors. Objectives of this study are to increase spontaneous request and decrease challenging behavior among children with autisme by introducing a secondary reinforcer during therapy based on ABA model. Secondary reinforcer has lower reinforcing value than the primary reinforcer. When the children tried but were unable to produce their targeted behavior, they were given the secondary reinforcer. The children were divided into two groups, five children in the intervention group and four children in the control group, and they were taught specific target requesting behavior (TRB) to request for a preferred item. Three children in the intervention group recorded an increase in spontaneous request and a reduction in challenging behaviors. Only two children from the control group recorded an increase in spontaneous request and a decrease in challenging behaviors. However, only children from the intervention group were able to maintain their performance during the generalization sessions. The results suggest that children respond differently to specific prompts and interventions. Future studies should focus on how prompts affect children’s performance and also on reinforcer selection. Bigger scale studies are still needed to further determine the effectiveness of a secondary reinforcer in assisting the learning of requesting skill and in reducing challenging behaviors among children with autisme during therapy based on ABA model.